Updating Osteonecrosis of the Femoral Head - Young-Seung Ko; Joo Hyung Ha; Jung-Wee Park; Young‐Kyun Lee; Tae-Young Kim; Kyung‐Hoi Koo (2023)
Osteonecrosis of the femoral head (ONFH), a condition characterized by the presence of a necrotic bone lesion in the femoral head, is caused by a disruption in the blood supply. Its occurrence is more common in young and middle-aged adults and it is the main reason for performance of total hip arthroplasty in this age group. Its incidence is increasing along with increased use of glucocorticoids for management of adjuvant therapy for treatment of leukemia as well as organ transplantation and other myelogenous diseases. Current information on etiology and pathogenesis, as well as natural history, stage system, and treatments is provided in this review. A description of the Association Research Circulation Osseous (ARCO) criteria for classification of glucocorticoids- and alcohol-associated ONFH, 2019 ARCO staging system, and 2021 ARCO classification using computed tomography for the early stages of ONFH is also provided.